INDOCTRINATION AND BRAINWASHING PROCESS IN THE CASE OF TERRORISM: A PSYCHOLOGICAL ANALYSIS OF SUICIDE BOMBING IN SURABAYA, EAST JAVA - Mohammad Takdir (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2020)
This paper analyses the process of indoctrination and brainwashing in the case of terrorism. This study uses a psychological approach to uncover the suicide bombing case in Surabaya which has happened in Mei 2018. By using a case study, this research effort to understand deeply the psychological phenomenon that encourages terrorists to invite their families like suicide bombers. This research shows that the indoctrination process is done by giving video on jihad. This indoctrination process is an important stage in the cultivation of radical ideologies through pre-radicalization, self-identification, and jihadization. In this study, it was found that there are some stages of brainwashing for suicide bombers, namely the recruitment process, the indoctrination stage, and the isolation to do an attack of suicide bombing. Key Word: Brainwashing, Indoctrination, Suicide Bombing, Terrorism